Energy-dissipation in Seismic Retrofit RC Building with Friction Dampers - Panumas Saingam; Nitikorn Sangswang; Pana Sansombat (My University, 2023)
Reinforced concrete (RC) buildings have suffered severe damage in the past due to inadequate lateral force resistance or energy dissipation capability. There is a need to improve the seismic performance of existing, vulnerable RC structures, particularly those that were either not initially intended for seismic effects or were planned to an obsolete seismic standard. Friction dampers are a revolutionary technique for improving lateral force resistance and energy dissipation capacity in the seismic retrofit of RC buildings. In this study, energy dissipation in seismically retrofitted RC buildings using friction dampers is investigated. An investigation of the nonlinear response history was performed after friction dampers were applied to the RC building. The analysis results indicate that the peak story drift ratios are reduced and constant throughout the height of the building, which may be a sign that the structure has not suffered soft story damage. In addition, the total friction damper’s energy-dissipation is half of the total input energy.
Keywords: Seismic energy; Seismic Performance and Analysis